Hypoxia-induced IL-32β increases glycolysis in breast cancer cells. Issue 2 (28th January 2015) - Park, Jeong Su; Lee, Sunyi; Jeong, Ae Lee; Han, Sora; Ka, Hye In; Lim, Jong-Seok; Lee, Myung Sok; Yoon, Do-Young; Lee, Jeong-Hyung; Yang, Young
Highlights: Hypoxia-induced ROS increase IL-32β expression. IL-32β enhances glycolytic pathway through increase of LDH activity under hypoxic conditions. Inhibition of hypoxia-induced IL-32β impairs tumor cell growth. IL-32β increases Src activity via protecting the dephosphorylation of Src by PP2A. Abstract: IL-32β is highly expressed and increases the migration and invasion of gastric, lung, and breast cancer cells. Since IL-32 enhances VEGF production under hypoxic conditions, whether IL-32β is regulated by hypoxia was examined. Hypoxic conditions and a mimetic chemical CoCl2 enhanced IL-32β production. When cells were treated with various inhibitors of ROS generation to prevent hypoxia-induced ROS function, IL-32β production was suppressed by both NADPH oxidase and mitochondrial ROS inhibitors. IL-32β translocated to the mitochondria under hypoxic conditions, where it was associated with mitochondrial biogenesis. Thus, whether hypoxia-induced IL-32β is associated with oxidative phosphorylation (OXPHOS) or glycolysis was examined. Glycolysis under aerobic and anaerobic conditions is impaired in IL-32β-depleted cells, and the hypoxia-induced IL-32β increased glycolysis through activation of lactate dehydrogenase. Src is also known to increase lactate dehydrogenase activity, and the hypoxia-induced IL-32β was found to stimulate Src activation by inhibiting the dephosphorylation of Src. These findings revealed that a hypoxia-ROS-IL-32β-Src-glycolysis pathway is associated with the regulation of cancer cell metabolism.